APPLICATION OF CENTRAL COMPOSITE DESIGN FOR OPTIMIZATION OF EFFERVESCENT FLOATING TABLETS USING HYDROPHILIC POLYMERS - Mohapatra, Snehamayee; Sahoo, Sunit Kumar; Kar, Rajat Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The aim of the present study was to optimize effervescent floating tablets of Cefixime Trihydrate as model drug by optimization of polymers concentration using central composite design. Mean dissolution time (MDT), time required to release 50% of drug (t50%), drug release at 2Â h (R2h) and dissolution efficiency in 2 h (DE2h) were taken as target responses, where as the quantity of different polymers such as Carbopol 934P (viscoelastic agent), Sod.CMC (swelling agent) were considered as independent variables. A second-order polynomial equation was determined by the multiple regression analysis of the experimental data. The best fitting model was selected based on the comparisons of the coefficient of determination (r2), adjusted coefficient of determination (adj. r2). In addition, analysis of variance (ANOVA) was used to evaluate the statistical significance of the quadratic polynomial model. The optimum values for the critical components were obtained as 13.151% Carbopol 934P and 4.08% of Sod.CMC with predicted value of 4.926 h MDT, 5.257 h t50%, 27.6316% R2h and 16.5951% DE2h from desirability and overlay plot. Further the reliability of the model was checked by validating the observed responses from optimized formula. The drug release from characteristics of all formulations followed Higuchi model with a non-Fickian diffusion mechanism. Further the data of FTIR study showed there was no interaction of drug and excipients used for the preparation of floating tablets. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Key words: Central composite design, Cefixime Trihydrate, Mean dissolution time, Fickian diffusion, dissolution efficiency